An open-access, very-low-field MRI system for posture-dependent 3He human lung imaging - Tsai, L.L.; Mair, R.W.; Rosen, M.S.; Patz, S.; Walsworth, R.L. (Journal of magnetic resonance (1997), 2008)
We describe the design and operation of an open-access, very-low-field, magnetic resonance imaging (MRI) system for in vivo hyperpolarized 3He imaging of the human lungs. This system permits the study of lung function in both horizontal and upright postures, a capability with important implications in pulmonary physiology and clinical medicine, including asthma and obesity. The imager uses a bi-planar B 0 coil design that produces an optimized 65 G (6.5 mT) magnetic field for 3He MRI at 210 kHz. Three sets of bi-planar coils produce the x, y, and z magnetic field gradients while providing a 79-cm inter-coil gap for the imaging subject. We use solenoidal Q-spoiled RF coils for operation at low frequencies, and are able to exploit insignificant sample loading to allow for pre-tuning/matching schemes and for accurate pre-calibration of flip angles. We obtain sufficient SNR to acquire 2D 3He images with up to 2.8 mm resolution, and present initial 2D and 3D 3He images of human lungs in both supine and upright orientations. 1H MRI can also be performed for diagnostic and calibration reasons.